Soil moisture and its effect on bulk density and porosity of intact aggregates of three Mollic soils - ENKOVA, LUCIA KO; URÍK, MARTIN (The Indian Journal of Agricultural Sciences, 2012)
The obtained results confirmed the changes in bulk density, and thus in porosity resulting from the change in soil water content. The bulk density of aggregates of three Mollic soils increased with decreasing content of water in samples, although there were differences among particular soil types. The aggregates of haCH showed a rather steady increase in bulk density with decrease in moisture content, aggregate bulk density of mogmVRpe remained unchanged after heating at 50°C for 24 hr, heating to 50°C even after a prolonged period had no effect on bulk density of ccmoFL clods.